2018
DOI: 10.1177/0361198118777602
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Highway Capacity Estimation Methods

Abstract: The capacity of a freeway segment is a critical factor for planning, design, and operational analysis of freeway facilities. This research aimed to perform a comparison among well-known freeway capacity estimation methods in order to investigate their application, as well as their advantages and disadvantages. Single estimate capacity methods such as the Van Aerde method, and breakdown probability methods, such as the product limit method (PLM), the Highway Capacity Manual (HCM) method, and the sustainable flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 8 publications
1
9
0
1
Order By: Relevance
“…Further comparison between the optimum volumes and the conventional capacity values indicated that the optimum volume is a reasonable estimator of freeway design capacity. This was also supported by other researchers ( 16 – 18 ).…”
Section: Literature Reviewsupporting
confidence: 88%
“…Further comparison between the optimum volumes and the conventional capacity values indicated that the optimum volume is a reasonable estimator of freeway design capacity. This was also supported by other researchers ( 16 – 18 ).…”
Section: Literature Reviewsupporting
confidence: 88%
“…The definition of capacity has been studied extensively in the literature (14)(15)(16)(17). Generally, as flow increases, the speed gradually decreases until the breakdown phenomenon occurs.…”
Section: Methodsmentioning
confidence: 99%
“…Effectively measuring freeway performance requires accurate estimation of capacity. Asgharzadeh and Kondyli ( 3 ) compared well-known capacity estimation methods, listing their advantages and disadvantages: Van Aerde ( 4 ), product limit method ( 5 , 6 ), Sustainable Flow Index ( 7 ) and HCM 6th edition ( 1 ). With the exception of Van Aerde, all methods rely on breakdown identification, which brings the substantial advantage of addressing the stochastic nature of capacity.…”
Section: Literature Reviewmentioning
confidence: 99%